A framework of Virtual Reality learning system for teacher’s trainee programme at Malaysian higher education / Nurshamshida Md Shamsudin and Faizah Abdul Majid - Md Shamsudin, Nurshamshida; Abdul Majid, Faizah (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
Mobile Virtual reality (VR) learning based has contributed effectively to various disciplines since its implementation in education. However, current pedagogical methods and tools at the tertiary level are unable to provide students with realistic and practical usage of virtual reality due to incompetency and lack of IT skills among educators. The current problem with mobile learning is the visualization and content presented in the application, where it may not be appealing for the student to use because it is mostly text-based. The next issue regarding learning is the user interface where it may not be usable to a non-experience user, and most important is the framework available for the mobile-Virtual Reality Learning System is still limited. This study proposes a framework for using Virtual Reality (VR) system for experiential learning. The framework consists of the following three modules: VR Teacher’s Module Knowledge Dissemination, VR Teacher’s Learning Preparation Module and VR Teacher’s Module Knowledge Assessment. The system prototype will be developed and evaluated with case studies to identify the system’s benefits and limitations.